Openwork@Dendritic Mesoporous Silica Nanoparticles for Lactate Depletion and Tumor Microenvironment Regulation. Issue 49 (7th October 2020) - Tang, Jie; Meka, Anand Kumar; Theivendran, Shevanuja; Wang, Yue; Yang, Yannan; Song, Hao; Fu, Jianye; Ban, Wenhuang; Gu, Zhengying; Lei, Chang; Li, Shumin; Yu, Chengzhong
Abstract: The direct depletion of lactate accumulated in the tumor microenvironment holds promise for cancer therapy but remains challenging. Herein, we report a one‐pot synthesis of openwork@ dendritic mesoporous silica nanoparticles (ODMSNs) to address this problem. ODMSNs self‐assembled through a time‐resolved lamellar growth mechanism feature an openworked core and a dendritic shell, both constructed by silica nanosheets of ≈3 nm. With a large pore size, high surface area and pore volume, ODMSNs exhibited a high loading capacity (>0.7 g g −1 ) of lactate oxidase (LOX) and enabled intratumoral lactate depletion by >99.9 %, leading to anti‐angiogenesis, down‐regulation of vascular endothelial growth factor, and increased tumor hypoxia. The latter event facilitates the activation of a co‐delivered prodrug for enhancing anti‐tumor and anti‐metastasis efficacy. This study provides an innovative nano‐delivery system and demonstrates the first example of direct lactate‐depletion‐enabled chemotherapy. Abstract : A one‐pot synthesis of openwork@dendritic mesoporous silica nanoparticles (ODMSNs) for depletion of lactase accumulated in the tumor microenvironment is reported. ODMSNs exhibited a high loading capacity of lactate oxidase and enabled intratumoral lactate depletion of over 99.9 %, leading to anti‐angiogenesis, down‐regulation of vascular endothelial growth factor, and increased tumor hypoxia.